Cross-sectional investigation of mycological diagnosis challenges in Saudi Arabia - Khateb, Aiah Mustafa; Alkhaibari, Shatha Ali (Frontiers in Cellular and Infection Microbiology, 2023)
Background The global incidence of fungal infection has increased dramatically over the last two decades. Fungal diseases threaten both immunocompetent, and immunocompromised patients. The current fungal diagnostics status in Saudi Arabia needs to be evaluated, especially with the increase of the immunosuppressed population. This cross-sectional study investigated the gaps in mycological diagnosis on a national level. Materials and methods The call interview questionnaire responses were collected to evaluate the demand for fungal assays, diagnostic methods’ quality, and mycological expertise of laboratory technologists in both public and private medical intuitions. The data were analyzed using (IBM SPSS ® software version 22.0). Results A total of 57 hospitals from all Saudi regions participated in the questionnaire; however, only 32% received or processed mycological samples. Most participants were from the Mecca region (25%), Riyadh region (19%), and Eastern region (14%). The top fungal isolates identified were Candida spp., Aspergillus spp., and dermatophyte. Fungal investigation is highly requested by intensive care, dermatology, and obstetrics and gynecology units. Most laboratories rely on fungal culture and microscopic examination, which mostly identify Candida to the genus level, and use 37°C incubators for culture (67%). Antifungal susceptibility testing (AST) and serological and molecular methods are rarely performed and mostly outsourced. Using accurate identification and AST are the primary factors to improve fungal diagnosis in respect to turnaround time and cost. The three major obstacles identified were availability of facility (47%), reagents and kits (32%), and good training (21%). Conclusions The results indicated that fungal diagnosis demand was relatively higher in high-population regions. This study highlighted the gaps in fungal diagnostics reference laboratories to encourage their improvement in Saudi hospitals.